Numerical investigation on the effect of balcony open and solid upstand on smoke contamination in atrium balconies - Mutafi, M.A. (Institute of Physics Publishing, 2017)
Atrium is a modern architectural design of buildings that has an open space at the middle and contains several floors. In atrium structure the smoke due to fire can easily flow through the open spaces and causes smoke contamination. CFD simulation using fire dynamic simulator (FDS) software is conducted in this work, to investigate the effect of balcony open upstand on smoke contamination in atrium's balconies and compare it with balconies with solid upstand. It was found that in case of open upstand, the smoke contamination occurrence decreased inside the balcony comparing with balconies with solid upstand. © 2017 Published under licence by IOP Publishing Ltd.